Christianity, politics, and public life in Kenya - Gifford, Paul (Columbia Univ. Press, 2009)
The context -- Mission Christianity, mainly Protestant -- Mission Christianity, mainly Catholic -- African independent (or instituted) churches, AICS -- Pentecostalism, some churches -- Pentecostalism, some issues -- A biblical Christianity -- A spirit Christianity -- A domesticated Christianity -- Conclusion